FEMALE REPRESENTATION IN ENGLISH LEARNING TEXTBOOK: CRITICAL DISCOURSE ANALYSES - Putri, I Gusti Ayu Vina Widiadnya; Widiadnya, I Gusti Ngurah Bagus Yoga; Irwandika, Gede (English Review: Journal of English Education, 2025)
This research aims to examine discourse components on the dynamics of female stereotype in texts. This research uses data taken from the Narrative text of an English textbook specifically designed for elementary school students in Indonesia. Books are considered a valuable source of scientific inquiry. This research uses a combination of data analysis techniques and field methods, especially by observations and interviews. The data collection strategy used in this research includes the use of questionnaires, interviews, and documentation of language forms contained in narrative texts in textbooks. The findings of this research show there are some aspects of discourse on the dynamics of female representation in students’ texts book, which include microstructure, macrostructure, and superstructure of the text. Microstructure includes grammatical components such as references, substitution, and conjunctions. The macrostructures are contained in context, circumstances, and culture that successfully represent women from different points of view. The superstructure of the text include orientation, complication and resolution. Data analysis reveals the prevalence of female stereotypes as evidenced by micro, macro, and superstructure.